PENGARUH KEPUASAN KERJA DAN KOMITMEN ORGANISASI TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB): (Studi Kasus RSU UKI) - Fanani, Iqbal; Djati, S.Pantja (Universitas Kristen Indonesia, 2016)
Research conducted at UKI Hospital to determine the effect of job satisfaction and organizational commitment on organizational citizenship behavior. The purpose of this study was to determine the effect of job satisfaction and organizational commitment simultaneously and partially to organizational citizenship behavior of employees in the nursing section UKI Hospital. Data obtained through questionnaires and interviews with HR staff. This research was conducted at UKI Hospital. The method used is a method of distributing a questionnaire with a sample of 65 employees and data analysis using Spearman Rank correlation analysis, correlation, and hypothesis testing .. The results of t test (partial) shows that (1) job satisfaction partially influence on OCB. This is indicated job satisfaction t value of 2.722 is greater than t table amounted to 1,998 and obtained significance value of 0.008 <0.05 then Ho is rejected. (2) organizational commitment partially but not significant effect on OCB. This is demonstrated organizational commitment t value of 1.615 is smaller than t table amounted to 1,998 and obtained significance value of 0.111> 0.05 then Ho is accepted. Test research results f (simultaneously) shows that job satisfaction and organizational commitment together or simultaneously influence OCB variable. It is shown the value of f count of 7,650 is greater than f table by 3.15 and obtained significance value of 0.001 <0.05, Ha accepted.Keyword: Job Satisfaction, Organizational Commitment, and Organizational Citizenship Behavior are low in UKI Hospital Employees